Political science quarterly ([New York, etc.] Academy of Political Science.)
Vols. 4-38, 40-41 include Record of political events, Oct. 1, 1888-Dec. 31, 1925 (issued as a separately paged supplement to no. 3 of v. 31-38 and to no. 1 of v. 40).
International index^ Poole's index to periodical literature^ Social sciences & humanities index
Book review digest
Index of economic articles in journals and collective volumes
Journal of economic literature
Social sciences index
ABC pol sci
Keywords: Social sciences -- Periodicals